Physical exercise and functional fitness in independently living vs institutionalized elderly women: a comparison of 60- to 79-year-old city dwellers - Furtado HL (Dove Medical Press, 2015)
Hélio L Furtado,1 Nelson Sousa,2 Roberto Simão,3 Fabio Dutra Pereira,1 José Vilaça-Alves2 1Castelo Branco University, Rio de Janeiro, Brazil; 2Research Center for Sport, Health, and Human Development, University of Trás-os-Montes and Alto Douro, Vila Real, Portugal; 3School of Physical Education and Sports, Rio de Janeiro Federal University, Rio de Janeiro, Brazil Purpose: To compare functional fitness (FF) levels among independent-living (IL) and day care (DC) elderly women of different age groups and to analyze changes in FF after 8 months of participation in an exercise program intervention for the IL elderly women. Materials and methods: A total of 674 elderly women were divided into four IL groups with age in the range of 60–64 years (IL60–64, n=149), 65–69 years (IL65–69, n=138), 70–74 years (IL70–74, n=135), and 75–79 years (IL75–79, n=83), and four DC groups with age in the range of 60–64 years (DC60–64, n=35), 65–69 years (DC65–69, n=34), 70–74 years (DC70–74, n=47), and 75–79 years (DC75–79, n=53). The intervention consisted of a multimodal exercise training, 3 days per week for 8 months. Senior Fitness Test battery performances were obtained at baseline and after 8-month intervention. Results: Significant differences were identified between all IL groups and DC groups in all FF tests (P<0.001), except between IL70–74 and DC70–74 in the chair sit-and-reach. Analysis of covariance (ANCOVA) identified significant improvements in all FF tests between pre- and posttests in the IL groups (P<0.001), except in the chair sit-and-reach for the IL70–74. ANCOVA also showed a significant declining performance in all FF tests for DC groups (P<0.001), except in the chair sit-and-reach for the DC70–74 and DC75–79. Conclusion: IL women are more fit than institutionalized DC elderly women. The multimodal training was effective in improving all FF components related to daily living activities, in all age groups. In contrast, institutionalized elderly showed a clear tendency to worsen their FF over the time. Keywords: aging, multimodal training, physical activity, older women, day care